A grammar of Kurtöp - Hyslop, Gwendolyn ca. 20./21. Jh (Brill's Tibetan studies library, 2017)
A grammar of Kurtop' is the first descriptive grammar of Kurtop, a threatened language of Bhutan, and the only reference grammar of any East Bodish language. The East Bodish languages are a relatively unstudied branch of the larger Tibeto-Burman family, situated in Bhutan and neighbouring regions in Tibet and Arunachal Pradesh. The chapters introduce the language and the people who speak in a historical context and then go on to detail the synchronic and diachronic phonology, discuss word classes and cause structure, morphosyntax and syntax, and illustrate rich system of evidentiality and related categories. The book will be of interest to Tibeto-Burmanists, historical linguists and those interested in the prehistory of the eastern Himalayas, and to typologists.